2015
DOI: 10.1099/jmm.0.000119
|View full text |Cite
|
Sign up to set email alerts
|

SCCmec IX in meticillin-resistant Staphylococcus aureus and meticillin-resistant coagulase-negative staphylococci from pigs and workers at pig farms in Khon Kaen, Thailand

Abstract: Livestock-associated meticillin-resistant Staphylococcus aureus, clonal complex (CC) 398, has been reported in Europe, whereas CC9 MRSA has mostly been found in Asia. Therefore, we aimed to detect MRSA on pig farms in north-eastern Thailand. A total of 257 nasal swabs (159 samples from pigs and 98 from pig-farm workers) were collected from three pig farms in north-eastern Thailand from 2010 to 2011. MRSA isolates were confirmed for femA and mecA genes by PCR. The MICs of eight antimicrobials, namely vancomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…A relatively high frequency of ccrC positive SCCmec was found in S. hominis, which suggests that S. hominis could serve as a reservoir for this type of SCCmec for S. aureus (Mendoza-Olazaran et al, 2013). A pseudo (Ψ) SCC element with a truncated ccrA gene located in the left extremity of the SCCmec identified in this study showed high similarity to a ΨSCC element found in type IX SCCmec of a ST9 MRSA isolate from Thailand (Anukool et al, 2011;Lulitanond et al, 2013;Sinlapasorn et al, 2015).…”
Section: Discussionmentioning
confidence: 56%
“…A relatively high frequency of ccrC positive SCCmec was found in S. hominis, which suggests that S. hominis could serve as a reservoir for this type of SCCmec for S. aureus (Mendoza-Olazaran et al, 2013). A pseudo (Ψ) SCC element with a truncated ccrA gene located in the left extremity of the SCCmec identified in this study showed high similarity to a ΨSCC element found in type IX SCCmec of a ST9 MRSA isolate from Thailand (Anukool et al, 2011;Lulitanond et al, 2013;Sinlapasorn et al, 2015).…”
Section: Discussionmentioning
confidence: 56%
“…In five publications from Thailand, methicillin resistant Staphylococcus aureus (MRSA) was investigated in pigs and pork meat [89,90,91,92,93]. In one study, a total of 104 pig farms were investigated for MRSA, alongside farmers and the farms′ environment.…”
Section: Resultsmentioning
confidence: 99%
“…The herd-level prevalence of MRSA was ~9.6%, and the individual pig and farmer prevalence was 0.7% and 2.5%, respectively [93]. All (100%) MRSA isolates were resistant to clindamycin, oxytetracycline, and tetracycline, while 100% were susceptible to vancomycin [92,93]. The Staphylococcal Cassette Chromosome mec (SCC mec ) clonal type IX appears to be quite disseminated in the Thai pig industry, representing a reservoir for human infection [91,92].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also did not find type VII SCC mec in CoNS in this study as other researchers; however, one isolate of type IX was disclosed in S. haemolyticus in clinic, which had not been previously confirmed in CoNS [ 12 , 23 ]. A recent study also reported SCC mec type IX in CoNS in the community [ 24 ]. Significantly, most CoNS strains recovered in this study (clinic and community) consisted of untypable SCC mec elements as many other reports [ 14 16 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 98%